Pendampingan Perencanaan dan Pengembangan Karir Siswa/I SMK di Era Digital - Sihombing, Ririsma; Ayu Pramesti, Nyoman Dira; Natalie, Jessica (Universitas Pahlawan Tuanku Tambusai, 2025)
The current Industrial Revolution is changing Indonesia's economic and geopolitical systems, by encouraging automation and collaboration between humans and artificial intelligence (AI). This change creates new needs in the world of work, such as the professions of Big Data Specialist and Robotic Engineer. Schools play an important role in equipping students to be ready to compete. However, most students of SMKN 5 Tangerang Regency do not yet understand the importance of career planning. The author and the school provide assistance for career planning and development. Activities are carried out through seminars, discussions, guidance groups, and technology-based approaches. As a result, students better understand their potential, are able to prepare career plans, and have a job description according to current industrial developments.